Assessing EFL learners' perceptions on the use of an educational software for English learning: an analysis of pedagogic and ergonomic features (Educación y Tecnología, 2015)
The present study aimed at analyzing EFL learners perceptions on the use of an educational software for language learning. A hundred and fifty-nine learners from the Agribusiness and Computer Science courses of an Integrated Technical High School Program participated in the study and rated the pedagogic and ergonomic features of the software in light of Sociointeractional and Structural Cognitive Modifiability theories of learning. Data were collected through questionnaires before and after software use. In general, the pedagogic qualitatively analysis revealed that Agribusiness and Computer students agreed that the software represents a relevant tool for EFL learning. The ergonomic analysis, on the other hand, indicated that some human-computer interaction features of the software are deficient. In sum, findings suggest that there must be a close relationship between the pedagogic and the ergonomic characteristics of the software if the aim is to foster language learning.
Keywords: educational software; EFL teaching and learning; pedagogical characteristics; ergonomics.